The situation of Animal Rabies in Nepal from 2013 to 2017 - Shahi, MK; Boonyo, K; Wongphruksasoong, V; Dhingra, M.S.; Upadhyaya, M; Kafle, S.K.; Koirala, P; Maharjan, M (Nepalese Veterinary Journal, 2023)
Available within full article